PENGARUH PEMAHAMAN KONSEP MATEMATIKA TERHADAP KECEMASAN DAN KEMANDIRIAN BELAJAR MAHASISWA TADRIS MATEMATIKA UINFAS BENGKULU - Feity Aisya; Umi Listiana; Rahadatul Aysi (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2023)
This study aims to determine the effect of the ability to understand mathematical concepts with anxiety and independence in learning mathematics in Tadris Mathematics students at UIN Fatmawati Sukarno Bengkulu. A good understanding of mathematical concepts is an important aspect of learning mathematics, while anxiety and independent learning can affect performance and learning outcomes in mathematics. The approach used in this study is quantitative where this research uses a correlational research design. The sample used in this study was Tadris Mathematics students at UIN Fatmawati Sukarno Bengkulu Class of 2021 who are taking lectures this semester. The instruments used included testing the understanding of mathematical concepts, the mathematics anxiety questionnaire, and the mathematics learning independence questionnaire. The description of mathematical concepts is one of the key aspects in the success of learning mathematics mathematics. The results of the information analysis show that there is a significant relationship between the description of the concept and anxiety and learning independence. Students who have a better understanding of concepts tend to have lower levels of anxiety and greater levels of learning independence. These findings indicate that conceptual understanding has an important role in reducing anxiety and increasing student learning independence. This research makes a crucial contribution to our understanding of the factors that influence students' learning anxiety and independence in mathematics. The practical implication of this research is that learning approaches that promote effective understanding of concepts can help reduce students' anxiety and increase their learning independence. Therefore, it is important for students in the Tadris Mathematics study program as prospective mathematics teachers to consider understanding concepts as a relevant factor in supporting learning success.